ELBOW WRAP IMPROVES BENCH PRESS PERFORMANCE IN TRAINED SUBJECTS - Gomes,Willy Andrade (2018)
ABSTRACT Introduction: The elastic wrap is widely used by different types of athletes and recreational practitioners of strength training in order to improve weightlifting performance. Objective: The objective was to investigate the acute effects of elbow wrap on strength performance, absolute volume, and rating of perceived exertion/discomfort during the bench press (BP) exercise. Methods: The experimental protocol was divided into three laboratory sessions. At the first session, a bench press familiarization phase was performed with (EW) and without (WEW) elastic elbow wrap. During the second session, the 1RM test was carried out in the bench press exercise under both EW and WEW conditions. At the third session, the repetition maximum (RM) test at 70% of 1RM (EW and WEW) was performed until concentric failure. After each session, subjects were consulted about their rate of perceived exertion (RPE), and discomfort (PSD). A paired student t-test was used to compare the values of 1RM and RMs with and without elastic wraps. Descriptive analysis was used for RPE and PSD. Results: For the 1RM test, there was a significant increase for the EW condition when compared to WEW (p<0.05). In the RMs test and absolute volume calculation, there was a significant increase for the EW condition (p<0.05). RPE did not differ in any of the conditions tested (p>0.05). PSD presented a high degree of discomfort with elastic wraps in all conditions. Conclusion: Elastic elbow wraps increase the load lifted in the 1RM test, and the maximum number of repetitions during the BP exercise, and consequently, the absolute volume. The elastic elbow wrap does not alter the subjective perception of effort, but it increases discomfort during exercise.